Rune Stones as Material Relations in Late Pagan and Early Christian Scandinavia - Lund, Julie (Danish Journal of Archaeology, 2020)
In this article, the material qualities and the use of space on rune stone and its links to the landscape during the Viking Age and in the Early Medieval Period in South Scandinavia are explored and related to acts of commemoration and changing spatial perceptions. The 11th century rune stones from Denmark and Scania without iconography have previously received less scholarly attention by the archaeologists, but here they form the main focus. Whereas the commemorative aspects of the rune stones have been noticed by a number of scholars, less emphasis has been on their material qualities and the spatial aspects of the inscription on the stones; the spatial references in the rune stones to the surrounding landscape; and the bodily effect they had for the readers of the runes. The rune stones are studied as expressions of social relations between living, deceased and places in late pagan and early Christian Scandinavia. Three phenomena are explored: the rune stones at bridges and the role of the bridge in paganism and Christianity; the use of the surface and shape of the stones to separate diverging beings; and the shape of the inscription and its relation to the new concepts of afterworld in terms of heaven above, while simultaneously creating links to near and distant pasts. Further, the process of creating relations to distant pasts in the Early Christian period is explored.